HUBUNGAN ANTARA POWER OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS XI IPS SMAN 3 KECAMATAN TAPUNG KABUPATEN KAMPAR - Johendri, Apriyanto; ', Saripin; Nita, Ni Putu Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this researil is less than the maximum power of leg muscle results in long jump squat style. This is in because by the factor of the physical condition of male students in class XI IPS is still lacking, especially on the power leg muscle or explosive power visible when male students do repulsion, results tolakannya less than the maximum is still flat and lacking in high jump, so the results his repulsion not optimal and does not in accordance with the expected. The sample in this study is the son of class XI student of SMAN 3 IPS Tapung Districts of Kampar regency. A sampling technique that the overall population (total sampling). The instrument used in this study is the Standing broad jump test, which aims to measure the strength of leg muscle power and then test the skill test long jump squat style that aims to measure the distance of a jump away. After that, the data is processed with statistical, normality test with lilifors test at significant level 0,05α. The hypothesis is that the alleged relationship between Power Muscles are the result of long jump leg squat style at boy students of class XI IPS SMAN 3 Tapung Districts of Kampar regency. Based on analysis of test lilifors produce L0maks (x) of 0.099 and 0.161 Ltabel, L0maks (y) of 0.150 and 0.161 Ltabel, means L0maks <Ltabel, then the samples come from normal populations distributed. Then from the calculation of product moment correlation between muscle power leg with the results of the long jump style squat where rhitung(0.089) <rtabel (0.374) means that the hypothesis is rejected and there is no relationship between muscle power leg with the results of the long jump on a male student of class XI IPS SMAN 3 Tapung Districts of Kampar Regency. There was no relationship here does not mean there is no relationship, although therelationship here is very low orweak Keywords: Power Relations leg muscle premises Results jump away.